Manfaat Perawatan Metode Kanguru terhadap Fungsi Fisiologis Bayi Prematur dengan Dukungan Ventilasi Mekanik - Merita Basril; Yeni Rustina (Journal of Telenursing (JOTING), 2022)
This study aims to identify the benefits of kangaroo care on the physiological function of premature infants with mechanical ventilation support. The method used is a systematic review through article searches on Proquest, ScienceDirect and Ebsco data sources. The results showed that the kangaroo method of care intervention in premature infants who were mechanically ventilated was not only safe but also stabilized and improved physiological function. In conclusion, the kangaroo care method provides benefits and is safe to be implemented in infants with mechanical ventilation. Keywords: Premature Babies, Physiological Functions, Kangaroo Method Care, Mechanical Ventilation